STRATEGI PERWUJUDAN KOTA BANDUNG SEBAGAI KOTA RAMAH PENYANDANG DISABILITAS: SEBUAH PERSPEKTIF AKSESIBILITAS PELAYANAN PUBLIK - Joni Dawud; Siti Widharetno Mursalim; Endah Tri Anomsari; Nur Imam Taufik (Jurnal Administrasi Negara, 2019)
The basis of this research begins with problems related to services for persons with disabilities that occur especially in the city of Bandung. Indonesian citizens with disability have the right to live independently. The right can only be fulfilled if the accessible public facilities are sufficiently available. Understanding the needs, Bandung City government has set a plan to transform the city into a disability-friendly one by taking several actions, most notably is building public facilities which can be used by everyone. However, the empirical data gathered on the field showcases that public facilities are not accessible by people with disability yet, particularly since they have not met the universal design which applies internationally. The approach in this study is qualitative by conducting observations, in-depth interviews and literature studies. As for the results of the study, there are challenges and strategies to transform Bandung into a disability-friendly city. There are several apparent challenges, such as how bureaucracy and society in the city are lack of awareness about the rights of people with disability. The coordination and communication among actors who are involved in public facilities development are not efficient yet, which results in the ineffective implementation of public service provision. The change of regional legislative and executive head also influences the progress of regional law-making regarding public service which is more considerate of people with disability.In the midst of the challenging situation, realising Bandung as a disability-friendly city is a plausible goal to achieve, with the appropriate strategies as its condition. This research aims to discuss strategies that can be used to transform Bandung into a disability friendly city.